2014
DOI: 10.1007/s10071-014-0799-z
|View full text |Cite
|
Sign up to set email alerts
|

Does urbanization facilitate individual recognition of humans by house sparrows?

Abstract: Wild animals living in proximity to humans may benefit from recognizing people individually and adjusting their behaviour to the potential risk or gain expected from each person. Although several urban-dwelling species exhibit such skills, it is unclear whether this is due to pre-existing advanced cognitive abilities of taxa predisposed for city life or arises specifically in urban populations either by selection or through ontogenetic changes facilitated by exposure to humans. To test these alternatives, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 36 publications
1
22
1
Order By: Relevance
“…This lack of differentiation between the familiar hostile and unfamiliar person indicates that great tits either did not recognize the people or perceived them as equally threatening. Although the ability to recognize individual humans is often associated with particularly intelligent species such as corvids (Lee et al, ; Marzluff et al, ), it has also been demonstrated in other birds like passerines and pigeons (Belguermi et al, ; Levey et al, ; Vincze et al, ). Great tits often perform well in learning and problem‐solving tasks (Preiszner et al, ; Sasvári, ); thus, if individual recognition of humans is part of a more general set of cognitive abilities, great tits are likely to have the cognitive capacity for it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This lack of differentiation between the familiar hostile and unfamiliar person indicates that great tits either did not recognize the people or perceived them as equally threatening. Although the ability to recognize individual humans is often associated with particularly intelligent species such as corvids (Lee et al, ; Marzluff et al, ), it has also been demonstrated in other birds like passerines and pigeons (Belguermi et al, ; Levey et al, ; Vincze et al, ). Great tits often perform well in learning and problem‐solving tasks (Preiszner et al, ; Sasvári, ); thus, if individual recognition of humans is part of a more general set of cognitive abilities, great tits are likely to have the cognitive capacity for it.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we suggest that differentiating between humans might have little ecological relevance for both urban and forest great tits, for two reasons. First, recognizing individual humans may be the most relevant in habitats with low but non‐negligible human population density (such as farmlands) where repeated encounters with the same individual humans are likely (Vincze et al, ). In forest habitats, encounters with humans are very uncommon, whereas in cities, only few of the many people may be encountered repeatedly, at least in public areas like our study sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Papp et al , Vincze et al. ). The experiment presented here is built on this previous work and utilizes some of the data used in a previous paper that examined the predictors of individual problem‐solving performance (Bókony et al.…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a more general project that explores the causes and consequences of behavioural flexibility in birds (B okony et al 2014;Papp et al 2015. The experiment presented here is built on this previous work and utilizes some of the data used in a previous paper that examined the predictors of individual problem-solving performance (B okony et al 2014(B okony et al , Papp et al 2015. However, the two papers report two entirely different sets of analyses investigating separate research questions, and there is no overlap in the presented results.…”
Section: Methodsmentioning
confidence: 99%